2017
DOI: 10.1017/aae.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Research, Productivity, and Output Growth in U.S. Agriculture

Abstract: Abstract. This article reviews the current debate on whether U.S. agricultural productivity growth is slowing. It also assesses recent research on how productivity is related to long-term investment in research and development (R&D). It describes significant changes taking place in the U.S. agricultural research system, including the growing role of private agribusiness as a main developer of new agricultural technologies and what this implies for agricultural science policy. The conclusion has suggestions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 72 publications
1
50
0
Order By: Relevance
“…Oehmke () and Fuglie et al. () argue the mirr assumes a suboptimal reinvestment response and is sensitive to project horizon. Oehmke contends the suboptimality consists in reinvesting at a rate lower than borrowing cost, since present‐value loan cost would have been reduced by paying back the loan.…”
Section: Characterizing India's Agricultural Technologymentioning
confidence: 99%
“…Oehmke () and Fuglie et al. () argue the mirr assumes a suboptimal reinvestment response and is sensitive to project horizon. Oehmke contends the suboptimality consists in reinvesting at a rate lower than borrowing cost, since present‐value loan cost would have been reduced by paying back the loan.…”
Section: Characterizing India's Agricultural Technologymentioning
confidence: 99%
“…Some of this enhanced variability is explained by specific exogenous events, such as the 1973 energy crisis and the US government's 1983 Payment-In-Kind (PIK) program. On the other hand, some of the variability has been casually associated with extreme weather events such as severe droughts and floods in key agricultural areas (26). For example, TFP rates declined sharply in 1993, when persistent heavy rain and thunderstorms caused drastic flooding in the Midwest.…”
mentioning
confidence: 99%
“…E-mail address: ludwik_wicki@sggw.pl; dr habil., WULS professor 515 agriculture (Alston et al, 2010;Gardner, 2002;Huffman and Evenson, 1993;Ruttan, 2002;Wang et al, 2015a). It has also been indicated that increase in agricultural productivity in the USA after year 1950 was significantly correlated with increase in TFP (total factor productivity) , while no significant correlation was found between the level of production inputs and the size of agricultural production (Fuglie et al, 2017). For developing countries, there is a significant gap in achievement of land productivity and work in agriculture, which is several decades long.…”
Section: Introductionmentioning
confidence: 99%